STEAM TECHNOLOGIES IN ENGLISH LESSONS - Irgasheva, Umida (Eurasian Journal of Academic Research, 2024)
The article explains the benefits of STEAM (Science, Technology, Engineering, Arts and Mathematics) technologies in teaching English as a foreign language. It shows how incorporating STEAM technologies into English lessons can provide a holistic learning experience that fosters creativity, critical thinking, and interdisciplinary connections. The integration of STEAM technologies in English lessons represents an innovative approach to teaching and learning. Traditionally associated with technical and scientific disciplines, STEAM technologies can enrich English education by fostering creativity, critical thinking, collaboration, and digital literacy. Here’s an exploration of how STEAM technologies are reshaping the landscape of English lessons. There are some ideas on how to integrate STEAM technologies into English lessons. The basis of modern approaches, the suggestions and recommendations for enhancing the information methodological support for the development of communicative, linguistic, sociolinguistic, pragmatic, speech and lexical competences with the help of STEAM technologies in teaching English are explained in the article.